Industrial Revolution In Agriculture And Manufacturing Sector 4.0 Whether It Has The Potential To Increase Value Added Tax Revenue: Case Study In Balkan - Pohan, Fawwaz Muhammad Zakli; Wijaya, Suparna (Educoretax, 2024)
The urgency of tax revenue in a country is something that is emphasized by the government. In this research, Value Added Tax revenue is the focus to be examined because it is related to many economic sectors. Therefore, the government tries to obtain tax revenue from various economic sectors to meet the country's targets and needs. This study aims to determine the impact of the agricultural sector and the manufacturing industry sector on Value Added Tax (VAT) revenues or what we know as Value Added Tax or VAT in the Balkan region on the European continent, with Foreign Direct Investment (FDI) moderation, through descriptive quantitative methods based on data from the World Bank. Through this research, it is found that the agricultural sector hurts VAT revenue, as well as the manufacturing industry sector which hurts VAT revenue. However, for the farming sector and the manufacturing industry sector which are moderated by the Foreign Investment variable, it is found that both do not affect revenue. Then the last moderation variable alone, namely Foreign Investment, does not affect revenue. It is hoped that this research will provide new insights related to the agricultural sector and the industrial sector with its influence on Value Added Tax revenue.